The Positive Impact of the ABLLS-R Model for Communication on Children with ASD at Al-Sibtain Academy for Autism and Developmental Disorders - Kadam, Sahar; Al-Khazraji, Nidaa (Al-Adab Journal, 2024)
This study explores aspects of communication in autistic children at Al-Sibtain Academy for Autism and Developmental Disorders. The main objective was to investigate whether the program and training methods of the academy positively impact the language development and communication skills of children enrolled in the program.To address this objective, a hypothesis was formulated: the program and training methods would significantly enhance language development in the attending children. A quantitative approach was employed, utilizing House's SCDS scale for analysis. The research design encompasses gathering numerical data through surveys, which is later subjected to statistical analysis. The findings indicate that the intervention had the greatest impact on children who engaged in daily activities tailored to their specific needs and commenced the program at an earlier age. This highlights the crucial role of early intervention and consistent therapy in promoting language development.In conclusion, this study underscores the effectiveness of Al-Sibtain Academy's program and training methods in fostering language development among autistic children. The results emphasize the significance of early intervention and sustained therapeutic efforts in maximizing positive outcomes.